Nitrogen uptake preference of cotton (Gossypium hirsutum L.) - James O. Latimer; Mark Farrell; Ben C. T. Macdonald (PLoS ONE, 2025)
Low molecular weight (LMW) soil organic nitrogen (N) can be a significant source of N in commercial cotton ( Gossypium hirsutum L.) systems, potentially comprising a meaningful portion of N uptake in Australian irrigated cotton. Cotton obtains the majority of its N from the soil N pool rather than directly from fertiliser—N. Organic N is the major component of the soil N pool. The purpose of this study was to test the ability of G. hirstutum to take up different organic and inorganic N forms using isotopically labelled compounds. This was done in a sand matrix to reduce potential for microbial competition and enable a clearer view of the physiological capacity of the plant to access different N forms. The experiment showed that cotton took up inorganic N (NO 3 - and NH 4 + ) and organic N (alanine and urea) concurrently, with a slight preference towards inorganic N overall. The uptake mechanism for organic carbon (C) associated with the organic N was also examined, showing that alanine—C was taken up linearly, with a consistent internal 13 C: 15 N ratio suggesting that some alanine was absorbed intact without extracellular deamination. Overall, the experiment demonstrated that G. hirsutum can rapidly and concurrently access different soil N pools, with a slight preference for inorganic N. The uptake mechanisms for organic N and C are complex, differing between compound types, and warrant further investigation. This study expands the list of plants known to utilise organic N to include commercial cotton, with implications for the management of N fertiliser in cotton growing systems.